Implementation of Administrative Management in the Development of Agribusiness Partnerships of Farmer Groups at the Agricultural Extension Center (BPP) of East Dumai District, Dumai City - Fara Shaliza; Nurul Hasana; Sinta Fransiska (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This Community Service Program (PKM) was motivated by the limited understanding and skills of farmer groups in managing administrative systems, which are essential prerequisites for developing agribusiness partnerships. Farmer groups under the supervision of the Agricultural Extension Center (BPP) of Dumai Timur District, Dumai City, have not yet implemented well-organized data recording and administrative management, resulting in low institutional readiness to establish agribusiness partnerships. This program aimed to apply administrative management practices to strengthen farmer group institutions and support the development of agribusiness partnerships. The methods used included extension activities through lectures, interactive discussions, and hands-on practice in preparing and managing farmer group administrative records. The results indicate an improvement in farmers’ understanding of the importance of administrative management in agribusiness partnerships, enhanced skills in organizing and maintaining administrative records, and the emergence of collective awareness of institutional governance. Furthermore, the program contributed to behavioral changes within farmer organizations, increased leadership roles among group administrators, and initiatives to develop more structured and sustainable agribusiness partnerships